Buffer management schemes for supporting TCP in gigabit routers with per-flow queueing. - Suter, B.
There has been much interest in using active queue management in routers in order to protect users from connections that are not very responsive to congestion notification. An Internet draft recommends schemes based on random early detection for achieving these goals, to the extent that it is possible, in a system without ?per-flow? state. However, a ?stateless? system with first-in/first-out (FIFO) queueing is very much handicapped in the degree to which flow isolation and fairness can be achieved. Starting with the observation that a ?stateless? system is but one extreme in a spectrum of design choices and that per-flow queueing for a large number of flows is possible, we present active queue management mechanisms that are tailored to provide a high degree of isolation and fairness for TCP connections in a gigabit IP router using per-flow queueing. We show that IP flow state in a router can be bounded if the scheduling discipline used has finite memory, and we investigate the performance implications of different buffer management strategies in such a system. We show that merely using per-flow scheduling is not sufficient to achieve effective isolation and fairness, and it must be combined with appropriate buffer management strategies
Keywords: IP flow state; Internet draft; TCP connections; Active queue management; Buffer management; Congestion notification; Fairness; Finite memory scheduling discipline; First-in/first-out queueing; Flow isolation; Gigabit IP router; Per-flow queueing; Per-flow scheduling; Performance; Random early detection; Stateless system